2014
DOI: 10.5812/ircmj.6577
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hyperlipidemia and Periodontal Infection

Abstract: Background:Periodontitis is a local chronic inflammatory condition of the supporting structures of the teeth resulting from a dental plaque biofilm attached to teeth surfaces. Recent studies have indicated that this oral disease may have effects on systemic health.Objectives:The aim of the present study was to evaluate the association between periodontitis and hyperlipidemia.Patients and Methods:This case-control study was conducted in Iran during March 2011. In this case-control study, levels of serum lipids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…When reviewing the literature on the relationship between periodontal conditions and the blood levels of lipoproteins in plasma, there are several scientific articles that affirm a positive relationship [37,[50][51][52][53]56]. Including the article by Pejcic et al, (2011) [50] verified that there were not a relationship, and also, a decrease on the lipid level after the periodontal therapy in patients with periodontitis, in a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When reviewing the literature on the relationship between periodontal conditions and the blood levels of lipoproteins in plasma, there are several scientific articles that affirm a positive relationship [37,[50][51][52][53]56]. Including the article by Pejcic et al, (2011) [50] verified that there were not a relationship, and also, a decrease on the lipid level after the periodontal therapy in patients with periodontitis, in a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al, (2010) [53] in addition to finding an increase of LDL and TG in patients with vascular diseases, the study also attempt for a presence of oral pathogens in plaques of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, periodontal disease, the major cause of tooth loss in adults, is caused by inflammatory processes that occur in gingival tissues in response to bacterial accumulation on the teeth. Chronic periodontitis is classified as slight, moderate, or severe periodontitis [ 1 , 2 , 3 ]. Recently, several studies have indicated that Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are the main pathogens associated with periodontal disease [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many other mechanisms have been hypothesized, none of which are widely accepted and still remain controversial. Existing literature on this topic increasingly indicates that high TC is a risk factor for periodontitis 20–24 …”
mentioning
confidence: 99%
“…Identification of potentially modifiable risk factors that play a role in development of this disease is instrumental in decreasing disease burden. Existing literature is limited in studying high TC as a risk factor for periodontitis, and most studies either had a small sample size or were conducted outside the United States 20,23‐26 …”
mentioning
confidence: 99%